Absorption, distribution, metabolism, and excretion of [14C]TPN729 after oral administration to rats. (2nd January 2022) - Cheng, Huan; Yu, Jinghua; Yang, Chen; Zhang, Ning; Fan, Zhen; Zhang, Xiaojuan; Wang, Junchen; Wang, Zhen; Zhong, Da-fang; He, Ji-Xiang; Yan, Shu; Diao, Xingxing
Abstract: TPN729, a novel phosphodiesterase type 5 (PDE5) inhibitor for the treatment of erectile dysfunction (ED), is in phase II clinical trials in China. Previous studies suggested that TPN729 possesses promising therapeutic value. In previous non-radiolabeled rat excretion studies, the recovery of TPN729 and its major metabolites accounted for approximately 8.58% of the administration dose in urine and faeces by 48 h post-dose. To solve this problem and further study the metabolism of TPN729 in rats, we used the radio-isotopic tracing technique for the first time. In this study, the mass balance, tissue distribution, and metabolism of TPN729 were evaluated in rats after a single oral dose of 25 mg/kg [ 14 C]TPN729 (150 μCi/kg). At 168 h post-dose, the mean total radioactivity recovery of the dose was 92.13%. Faeces was the major excretion route, accounting for 74.63% of the dose, and urine excretion accounted for 17.50%. After oral administration of [ 14 C]TPN729, radioactivity was widely distributed in all examined tissues, and a higher radioactivity concentration was observed in the stomach, large intestine, lung, liver, small intestine, and eyes. The concentration of drug-related materials were similar in plasma and blood cells. A total of 51 metabolites were identified in rat plasma, urine, faeces, and bile, and the predominant metabolically susceptible position of TPN729 was the pyrrolidine moiety. The main metabolic pathways were N -dealkylation, oxidation, and dehydrogenation. In summary, we solved the previous problem of low drug recovery, elucidated the major excretion pathway, determined the tissue distribution patterns, and investigated the metabolism of TPN729 in rats by using a radioisotopic tracing technique.